Fish swimming in turbulent waters : hydraulic engineering guidelines to assist upstream passage of small-bodied fish species in standard box culverts - Chanson, Hubert; Leng, Xinqian (Boca Raton : CRC Press, 2021)
Low-level river crossings, including culverts, are important for delivering a range of valuable socioeconomic services, including transportation and hydrological control. These structures are also known to have negative impacts on freshwater river system morphology and ecology, including the blockage of upstream fish passage, particularly small-body-mass fish species. Given the enormous environmental problems created by road crossings, new hydraulic engineering guidelines are proposed for fish-friendly multi-cell box culvert designs. The focus of these guidelines is on smooth box culverts without appurtenance, with a novel approach based upon three basic concepts: (I) the culvert design is optimized for fish passage for small to medium water discharges, and for flood capacity for larger discharges, (II) low-velocity zones are provided along the wetted perimeter in the culvert barrel, and quantified in terms of a fraction of the wetted flow area where the local longitudinal velocity is less than a characteristic fish speed linked to swimming performances of targeted fish species, and (III) the culvert barrel is smooth, without any other form of boundary treatment and appurtenance. The present monograph develops a number of practical considerations, in particular relevant to box culvert operations for less-than-design discharges. It is argued that upstream fish passage capabilities would imply a revised approach to maintenance, in part linked to the targeted fish species.This reference work is authored for civil and environmental engineers, as well as biology and ecology scientists interested in culvert design. While the book is aimed to professionals, the material is also lectured in postgraduate courses and in professional short courses.
Foreword (by Emeritus Professor Colin J. APELT) -- 1. Introduction -- 1.1 Presentation -- 1.2 Impact of road crossings -- 1.3 Culvert design, construction and operation -- 1.4 Structure of the monograph -- 2. Hydraulic engineering design of standard box culverts -- Current practice -- 2.1 Presentation -- 2.2 Design method and procedure -- 2.3 Hands-on application -- 2.4 Practical considerations -- 3. Fish passage in standard box culverts -- 3.1 Presentation -- 3.2 Physical modelling of fish passage: Basic dimensional considerations and similitude -- 3.3 Fish behaviour and kinematics in box culvert barrel -- 3.4 Discussion -- 4. Hydraulic engineering design for upstream fish passage in standard box culverts -- General concepts and design guidelines -- 4.1 Presentation -- 4.2 Basic concepts -- 4.3 Implementation of basic concepts -- 4.4 Design methodology -- 4.5 Simplified design guidelines -- 4.6 Discussion -- 5. Design application -- 5.1 Presentation -- 5.2 Case Study -- 5.3 Detailed application -- 5.3 Commentary and discussion -- 6. Discussion and practical considerations -- 6.1 Operation and maintenance of fish-friendly culverts -- 6.2 Alternatives to assist fish passage -- 6.3 Selection of the threshold discharge QT -- 6.4 Box versus pipe culverts -- 7. Conclusion -- APPENDICES -- Appendix A -- Glossary of technical terms -- Appendix B -- Hydraulic calculations of natural flood plain and less-than-design flow in a box culvert -- Appendix C -- On physical modelling of fish passage in standard box culverts -- Appendix D -- Computational Fluid Dynamics (CFD) Modelling of fish friendly standard box culvert barrel -- Appendix E -- On alternatives to improve upstream passage of small-body-mass fish, including retrofitting -- Appendix F -- Digital appendix: video movies of culvert operation and small-bodied fish swimming in box culvert channels -- AUTHOR INDEX -- SUBJECT INDEX -- REFERENCES -- Bibliography -- Internet bibliography
"A Balkema book."
OCLC-licensed vendor bibliographic record.
Keywords: Culverts; Fishes -- Migration; Fishways; TECHNOLOGY / Hydraulics